PRICE PERCEPTION: EFFECT OF COUPON PRONENESS AND SALE PRONENESS ON CONSUMER IMPULSE BUYING - Immanuel, Dewi Mustikasari; Mustikarini, Carolina Novi (Universitas Brawijaya, Indonesia, 2018)
The purpose of this research is to find out the consumer’s price perception by considering two factors, namely coupon proneness and sale proneness in order to know its influences on impulse buying of the consumer from one of the biggest department store retail company in Surabaya. Then, the researcher needs to take 385 respondents, which are taken from the infinite population of the department store’s consumer by utilizing questionnaire as a research instrument.The research is quantitative with the data analysis applies multiple regressions by using SPSS program. By the research, the researcher applies independent and dependent variables. The independent variable consists of coupon proneness and sale proneness. The dependent variable consists of impulse buying. The result of the research shows that there is a simultaneous effect of coupon proneness and sale pronenesstowardimpulse buying, however, there is no significant partially effect of sale proneness towards impulse buying. There are also many factors besides coupon proneness and sale proneness which also influence consumer impulse buying.